Estetika in liturgiese konteks –’n Basisteoretiese diskoers - Janse van Rensburg, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Aesthetics in Liturgical Context – A Fundamental Theoretical Discourse The science of esthetics has a long and complicated philosophical history. It is only recently that the discourse on art and interpretation has caught the attention of practical theologians, investigating the value of esthetics in liturgical context. This article endeavors to contribute to the discussion, by taking the debate further in identifying particular principles to be taken into account within a particular reformed liturgical theology.